MANAJEMEN PEMBINAAN ATLET PUSAT PENDIDIKAN DAN LATIHAN PELAJAR (PPLP) CABANG ATLETIK JAWA TENGAH DI SALATIGA TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study aims to determine how management coaching athletes Training and Education Center ( PPLP ) athletics in Salatiga , Central Java in 2013 . The approach used in this study is a qualitative approach . Data analysis technique used in this study are based on a descriptive qualitative analysis . Based on the research results that were in charge of the management board have areas of expertise and areas of expertise according to their respective duties and manage PPLP based on the book PPLP petujuk Implementation of Central Java . Recruitment of qualified coaches seen ( skill ) that is owned , experience in the field of athletics , as well as educational background , which most of them are teachers of physical education and health sports from elementary school through high school . Facilities and infrastructure PPLP athletic exercises used in Salatiga, Central Java, when viewed from the aspect of quality ( quality level eligibility ) is not sufficient , in terms of quantity can be said to be still lacking , the procurement and maintenance of facilities and infrastructure for training is a shared responsibility